Development and validation of a food frequency questionnaire to estimate the intake of genistein in Malaysia - Fernandez, A.R.; Omar, S.Z.; Husain, R. (2013)
Objective: To develop and validate a food frequency questionnaire (FFQ) to estimate the genistein intake in a Malaysian population of pregnant women. Method: A single 24-h dietary recall was obtained from 40 male and female volunteers. A FFQ of commonly consumed genistein-rich foods was developed from these recalls, and a database of the genistein content of foods found in Malaysia was set up. The FFQ was validated against 7-d food diary (FD) kept by 46 pregnant women and against non-fasting serum samples obtained from 64 pregnant women. Reproducibility was assessed by comparing the responses on two FFQs administered approximately 1 month apart. Results: The Pearson correlation coefficient between FFQ1 and FD was 0.724 and that between FFQ2 and FD was 0.807. Classification into the same or adjacent quintiles was 78 for FFQ1 versus FD and 88 for FFQ2 versus FD. A significant dose - response relation was found between FFQ-estimated genistein intake and serum levels. Conclusion: The FFQ developed is a reliable, valid tool for categorising people by level of genistein intake.